2020
DOI: 10.1002/cncr.32901
|View full text |Cite
|
Sign up to set email alerts
|

The impact of childhood cancer on parental separation, divorce, and family planning in Denmark

Abstract: Background: Childhood cancer is a devastating experience for the family. We aimed to assess the impact of having a child with cancer on parental separation, divorce, and future family planning in Denmark. Methods:We conducted a nationwide cohort study using Danish registry data. Parents of children diagnosed with cancer in 1982-2014 (n=7066 children, n=12418 case parents) were matched with ten comparison parents of cancer-free children (n=69993 children, n=125014 comparison parents). We used discrete-time Cox … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…While the effects are fairly small, are line with the most recent register-based evidence. Mader et al (2020) found slight reduction in risk of parental separation following child cancer using discrete-time hazard regression models. Interestingly, register-based evidence from 20 years ago (?…”
Section: S-9mentioning
confidence: 92%
“…While the effects are fairly small, are line with the most recent register-based evidence. Mader et al (2020) found slight reduction in risk of parental separation following child cancer using discrete-time hazard regression models. Interestingly, register-based evidence from 20 years ago (?…”
Section: S-9mentioning
confidence: 92%
“…The Civil Registration System and the unique personal identification numbers used in all Danish registries enabled accurate linkage of individual information across registries ( 15 ). The study population has previously been described ( 16 , 17 ), and detailed information is given in the online supplement ( Supplementary Methods , available online). Briefly, we identified 7636 children diagnosed with cancer before the age of 20 years in 1982-2014 from the Danish Cancer Registry ( 18 ) (see Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, having a child with cancer may negatively impact levels of income and employment status, which can put further strain on the family 6 . Childhood cancer has not been associated with an increased risk of separation or divorce among parents 7 . Still, the experience of parenting a child with cancer can be described as an exceptional situation for the whole family, with a likely impact on the couple relationship, for example, by changing the way parents talk to each other, 8,9 or by making sexuality and intimacy difficult 10 .…”
Section: Introductionmentioning
confidence: 99%
“…among parents. 7 Still, the experience of parenting a child with cancer can be described as an exceptional situation for the whole family, with a likely impact on the couple relationship, for example, by changing the way parents talk to each other, 8,9 or by making sexuality and intimacy difficult. 10 Parents may also struggle to give each other support in the distressing situation.…”
mentioning
confidence: 99%